Débattre pour apprendre en sciences expérimentales : le cas de la circulation sanguine - FATMA SAÏD; ALICE DELSERIEYS (Metaichmio Publications, 2016)
The present research questions the cognitive work of French upper secondary school students (14-15 years old) during a debate in science class. The debate is based on experimental manipulations related to bloodstream. The study follows the types of reasoning and the notion of truth brought by students and their cognitive displacement. For that, it uses indicators such as modelling and problematisation based on the study of language interactions used by the students considered. The importance of a debate during an empiric experimental situation in biology in the classroom is highlighted. The introduction of a discursive phase in such an experimental situation promoted the articulation between description, explanation and argumentation, and as a consequence, the construction of more elaborate hypotheses and explanatory models that were subjected to critic and experimentation.